Author Correction: Metabolism of multiple glycosaminoglycans by Bacteroides thetaiotaomicron is orchestrated by a versatile core genetic locus - Didier Ndeh (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.